2020
DOI: 10.1002/ldr.3715
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of primary productivity and rain use efficiency in terrestrial grassland ecosystems

Abstract: A comprehensive understanding of annual net primary productivity (ANPP) and rain‐use efficiency (RUE) along precipitation gradients is critial for grassland conservation under climate change. However, how ANPP and RUE respond to changes in precipitation at different spatial and temporal scales remains uncertain. The aim of this research was to clarify these things. Using data from 21 field experiments, with an average sampling period of 14.3 years in 32 sites, 18 of which are in China, we evaluated the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Furthermore, rainy years are likely to alleviate the negative effects of IPVI on drought stress compared with dry years (López-Rubio et al, 2022). However, our findings also indicated that above-ground biomass responses decreased from arid to humid regions, probably due to the decreasing rainfall use efficiency along a precipitation gradient (Yang et al, 2020). In addition, MAT had positive effects on community AGB response in arid grasslands, because increasing air temperature combined with precipitation pulse events may increase instantaneous ecosystem photosynthetic rates and alter plant phenology (Baldocchi et al, 2018;Fay et al, 2011;Quan et al, 2019).…”
Section: F I G U R Ementioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, rainy years are likely to alleviate the negative effects of IPVI on drought stress compared with dry years (López-Rubio et al, 2022). However, our findings also indicated that above-ground biomass responses decreased from arid to humid regions, probably due to the decreasing rainfall use efficiency along a precipitation gradient (Yang et al, 2020). In addition, MAT had positive effects on community AGB response in arid grasslands, because increasing air temperature combined with precipitation pulse events may increase instantaneous ecosystem photosynthetic rates and alter plant phenology (Baldocchi et al, 2018;Fay et al, 2011;Quan et al, 2019).…”
Section: F I G U R Ementioning
confidence: 55%
“…Environmental and edaphic factors played important roles in regulating total AGB response to IPVI in our study. Grasslands are generally limited by soil water availability (Heisler‐White et al, 2008; Yang et al, 2020), which is supported by the positive relationships of above‐ground biomass responses with MAP in arid grasslands and increased soil moisture across grasslands. Thus, IPVI is likely to enhance the variability of soil water availability and to increase the risk of soil water deficits under prolonged drought during the growing season; however, such effects may vary along a precipitation gradient (Hsu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent plots were 1.5 m apart. The distinction between the early and late growing seasons was determined by the phenology of common species at the study site (Yang et al, 2021a(Yang et al, , 2021b. The 60% change in the precipitation was based on the maximum value of historical precipitation records from 1954 to 2014.…”
Section: Experimental Designmentioning
confidence: 99%
“…In general, PUE may increase with MAP in arid regions, remains relatively constant under moderate precipitation levels and tends to show a downward trend when the MAP changes from extremely dry to extremely wet. On the temporal scale, a number of studies have found that PUE usually decreases with increasing annual precipitation (Bai et al., 2008; Yang et al., 2021a). Most studies have reported that PUE changes with MAP; however, few studies have reported how PUE changes with the alteration in precipitation timing.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation patterns influence ecosystem structure and function by affecting ecosystem water availability ( Huang et al., 2010 ; Schwinning et al., 2003 ; Scott & Biederman, 2017 ). For example, the alterations to precipitation patterns can affect rainfall use efficiency by changing the stem leaf ratio and ultimately impact plant productivity ( Yang et al., 2020 ). Altered precipitation patterns lead to the dominance of resource-conservative species with large root-shoot ratio and small specific leaf area ( Fay et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%